Grain Size Variations Record Segregation of Residual Melts in Slow‐Spreading Oceanic Crust (Atlantis Bank, 57°E Southwest Indian Ridge). Issue 4 (7th April 2021) - Ferrando, C.; France, L.; Basch, V.; Sanfilippo, A.; Tribuzio, R.; Boulanger, M.
Abstract: Beneath slow‐spreading ridges, melt bodies are generally considered to represent ephemeral magma reservoirs filled with crystal mushes. Formation of the oceanic crust requires at least partial extraction of melts from these crystal mushes. However, melts collection and extraction are processes yet to be fully constrained. We investigate olivine gabbros from the plutonic section recovered at the IODP Hole U1473A, in the Atlantis Bank Oceanic Core Complex (Southwest Indian Ridge), to unravel (i) the process of melt migration through lower crustal crystal mushes, and (ii) the collection and segregation of melts forming discrete microgabbro intervals. Throughout the Hole, fine‐ to coarse‐grained intervals are widespread in olivine gabbros. Along the contacts, coarse‐grained minerals display resorbed grain boundaries against the fine‐grained minerals, suggesting partial dissolution by the melt crystallizing the fine‐grained material. Coarse‐grained plagioclase and clinopyroxene are zoned, showing progressive chemical evolution from more primitive crystal cores to more evolved crystal rims. Fine‐grained minerals are unzoned and chemically similar to rims of coarse‐grained minerals, indicating a genetic relationship. We attribute significant enrichments in the most incompatible elements of plagioclase and clinopyroxene to a magma evolution process associated with reactive melt migration. As temperature decreased, melts residual from the reactive processes were segregated in magma pockets that ultimately crystallize the fine‐grained intervals (microgabbros). We document, for the first time, that these microgabbros are crystallization products of melts modified by reactive melt migration; the melts were extracted from the crystal mush and accumulated into discrete melt‐rich zones. This process could have promoted partial extraction of those melts that in turn potentially contribute to Mid Ocean Ridge Basalts erupted at the seafloor. Key Points: Geochemical zoning in coarse crystals record crystallization of primitive crystal mush and subsequent reactive melt migration thereof Fine‐grained olivine gabbros testify collection of residual melts from the crystal mush; their crystallization is dominated by nucleation Accumulation of migrating melts could have promoted extraction of those melts that potentially contribute to Mid Ocean Ridge Basalt erupted at the seafloor